2018
DOI: 10.1675/063.041.0110
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Flocks of Foraging Shorebirds During Spring Stopover at Delaware Bay, USA

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…17,19,20 During spring migration through Delaware Bay, some pairs of species differ in time of passage and such temporal separation is the most important variable for ecological segregation of species. 21 Nevertheless, in Fortescue, although several species also differed by arrival time, 49 all species started arriving there following the rise of Horseshoe Crabs and congregated in large numbers, when birds exhibited high degree of overlap both in use of microhabitats and feeding techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,20 During spring migration through Delaware Bay, some pairs of species differ in time of passage and such temporal separation is the most important variable for ecological segregation of species. 21 Nevertheless, in Fortescue, although several species also differed by arrival time, 49 all species started arriving there following the rise of Horseshoe Crabs and congregated in large numbers, when birds exhibited high degree of overlap both in use of microhabitats and feeding techniques.…”
Section: Discussionmentioning
confidence: 99%
“…During the reproductive season, female Horseshoe Crabs lay clusters of eggs on intertidal beaches of Delaware Bay, in the sand near the tide line, at depths ranging 5–30 cm. 50,51 At low tides, shorebirds are distributed around crab nests 23,52 but also, numerous birds are spread over the beach to prey upon eggs that are scattered over the intertidal zone by the receding water. 53 In this study, over 50% of foraging shorebirds were observed on sand and gravel away from the tide line, particularly turnstones, Sanderlings, and knots, which used this habitat significantly more compared to other habitats.…”
Section: Discussionmentioning
confidence: 99%
“…While competition has been well‐studied in ecology broadly, information on such interspecific interactions during migration remains rare (Moore and Yong 1991, Novcic 2018). Our results were consistent with this, uncovering only three studies on avian species that discussed co‐migrant competition.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, migrant bird species compete for these valuable foods. Some birds, like sanderlings C. alba , display aggressive behaviors towards other bird species as they race to eat the nutrient‐packed eggs (Novcic 2018). During co‐migrations across taxonomic groups, migrants could affect other migrant species through a range of interactions, including relationships characterized by: commensalism (when one species benefits and the other is not harmed); mutualism (when both species benefit); antagonism (when one species benefits at the expense of the other, such as through parasitism or predation); amensalism (when one species suffers a cost and the other is not affected); and competition (when both species experience negative effects while competing for resources).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential of wintering shorebirds to aggregate in recreational beaches, flocks with a high density of conspecifics are very competitive, and there may be reduced food availability per foraging area (Stinson 1980, Metcalfe and Furness 1986, Newton 2006, Novcic 2018. Greater monospecific flocks may also have lower feeding rates because of their disruption effect on prey (e.g.…”
Section: Introductionmentioning
confidence: 99%